Production of bioethanol from empty fruit bunches cellulosic biomass and Avicel PH-101 cellulose - Karim, R.A. (Springer Verlag, 2014)
Cellulosic ethanol production was carried out using empty fruit bunches (EFB) via simultaneous saccharification and fermentation (SSF) method. The EFB was pretreated with alkaline treatment using 0.2Â M of sodium hydroxide (NaOH) solution followed by mild acid hydrolysis using 3Â of sulfuric acid (H2SO4), and enzymatic saccharification using derived cellulose, Trichoderma reesei prior to fermentation using Saccharomyces cerevisiae. Acid hydrolysis-pretreated samples shows the best substrates to be used in fermentation since it can produce the highest amount of glucose and highest percentage of saccharification with 5.3Â mg/mL and 48Â , respectively. The EFB hydrolyzate obtained was subjected to fermentation under anaerobic condition. It was found that the highest ethanol yield was 0.42Â mg/mL from acid hydrolyze sample. Optimization of SSF was conducted on filter paper unit (FPU), pH and mass loading effect for bioethanol production. Highest ethanol productions from cellulose (Avicel PH-101) are 3.1, 3.7, and 4.6Â mg/mL using FPU 217, pH 4, and a 5.0-g cellulose loading accordingly. Â© 2014, Springer-Verlag Berlin Heidelberg.